Feasibility of Out-of-Hospital Cardiac Arrest Ultrasound by EMS Physicians. (4th May 2019) - Fitzgibbon, James B.; Lovallo, Emily; Escajeda, Jeremiah; Radomski, Marek A.; Martin-Gill, Christian
Abstract: Introduction : Point-of-care ultrasound (POCUS) has been suggested as a useful tool to predict survival and guide interventions in out-of-hospital cardiac arrest (OHCA). While POCUS has been deployed in prehospital settings, a minimal amount of data exists on prehospital use, particularly by personnel with limited ultrasound experience. We aimed to characterize the feasibility and barriers to prehospital POCUS during OHCA by emergency medicine services (EMS) physicians in training.Methods : We deployed the SonoSite iViz portable ultrasound device for use by EMS physicians for OHCA in an urban EMS system. All physicians received POCUS education as part of their graduate medical training and were provided an instructional video on use of the SonoSite iViz device. POCUS use was limited to identifying cardiac motion during pulse checks, without interrupting resuscitation, and the results could be used to supplement management at the physicians' discretion. Data were recorded prospectively by saving images on the device and through a custom electronic form within the patient care report. The primary measure was the frequency of use of POCUS during OHCA. Secondarily, we characterized agreement by expert (ultrasound fellowship trained) faculty (using a kappa statistic) and identified reported barriers to the use of prehospital POCUS.Results : From November 2016 to March 2017, 348 physician field responses were reviewed, including 127 cases of OHCA. There were 106 patients remaining in arrest on physician arrival, with 56 (52.8%) cases of POCUS use. Still or video images were recorded in 48 cases; video in 34 cases. From video images, agreement in identifying cardiac motion between the EMS physician and expert reviewer occurred in 91% of cases ( K  = 0.82). Reasons cited for not using POCUS included return of circulation soon before or after arrival, prioritizing clinical interventions, not having the ultrasound device, mechanical failure, and cessation of resuscitation per advanced directives.Conclusion : Use of POCUS by EMS physicians to detect cardiac activity in OHCA is feasible and correlates with expert interpretation. Several avoidable barriers were identified and should be considered in the future implementation of prehospital POCUS. Larger studies are needed to determine what role POCUS may play in prehospital cardiac arrest management.